Comparing the effectiveness of emotion regulation therapy and cognitive behavioral therapy on treatment adherence in hemodialysis patients: A randomized controlled clinical trial - Seyedeh Hanieh Salimi Arshad Moghaddam Pishkhani; Mohammad Javad Tarrahi; Fatemeh Zargar (PLoS ONE, 2025)
Introduction Non-adherence is a common challenge among patients undergoing hemodialysis (HD). This randomized controlled trial compared the efficacy of Emotion Regulation Therapy (ERT) and Cognitive Behavioral Therapy (CBT) on improving treatment adherence in hemodialysis patients, with a control group receiving standard care. Materials and methods Ninety hemodialysis patients were equally randomized into ERT, CBT, and control groups (N = 30 each group), with six attrition cases per group. Baseline demographics (age, BMI, dialysis duration, education) showed no significant intergroup differences (p > 0.05). Adherence was assessed across five domains: dialysis, medication, fluid intake, dietary regimen, and total adherence. A MANCOVA/ANCOVA model analyzed changes at pre-intervention, post-intervention, and 3-month follow-up, controlling for baseline characteristics. Results Both intervention groups demonstrated significant adherence improvements post-treatment versus controls (P < 0.001). CBT showed superior immediate effects, with total adherence scores increasing from 836.66 ± 192.95 to 1073.33 ± 89.28 (Δ + 28.3%), while ERT improved from 833.33 ± 210.53 to 920.00 ± 181.04 (Δ + 10.4%). At follow-up, CBT maintained higher adherence (1050.83 ± 93.88 vs. ERT’s 890.00 ± 155.30), though both groups experienced dialysis adherence declines from post-treatment peaks (CBT: 580 to 574.16; ERT: 520 to 483.33). Control group adherence deteriorated across all domains (total: 911.66 to 835.00). Time-intervention interactions were significant for total adherence (P < 0.001), dialysis (P = 0.006), and medication adherence (P < 0.001), with largest CBT effects on fluid restriction adherence (Δ + 56.1% vs. ERT’s Δ + 8.3%). Discussion While both therapies enhanced adherence, CBT produced greater short-term improvements, particularly in behavioral domains (fluid/dietary compliance), whereas ERT showed better maintenance of medication adherence. The differential trajectory patterns suggest CBT’s structured behavioral strategies may offer immediate benefits, while ERT’s emotion-focused techniques could support longer-term regimen acceptance. Integration of both approaches into renal care protocols may optimize adherence outcomes.